2017
DOI: 10.1063/1.4984244
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and electrowetting on corrugated substrates

Abstract: Wetting and electrowetting (EW) on corrugated substrates are studied experimentally and theoretically in this paper. On corrugated substrates, because of the anisotropy of surface morphology, the droplet shows an elliptical shape and the spreading velocities in different directions are different. Spreading of a droplet is usually controlled not only by the surface tensions but also by hemi-wicking. Our experimental results indicated that liquids along the grooves propagate much faster than those in the directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…After the maximum spreading, the droplet contact line pins at the edge of the wall of the hexagonal cavity. Similar behavior of the pinning of the contact line was reported on a corrugated surface and surface with protruded sharp edges, by Wang and co-workers 15,26 . While the droplet rebounds, the surface energy converts into the kinetic energy.…”
Section: Droplet Impact Dynamics Taro Leafsupporting
confidence: 83%
See 1 more Smart Citation
“…After the maximum spreading, the droplet contact line pins at the edge of the wall of the hexagonal cavity. Similar behavior of the pinning of the contact line was reported on a corrugated surface and surface with protruded sharp edges, by Wang and co-workers 15,26 . While the droplet rebounds, the surface energy converts into the kinetic energy.…”
Section: Droplet Impact Dynamics Taro Leafsupporting
confidence: 83%
“…They varied the pitch of the grooves and droplet impact velocity, and reported different fates of the impacting droplet, namely, no-bouncing, partial bouncing and complete bouncing. Wang and Zhao 15 and Wang et al 16 also experimentally investigated anisotropic wetting characteristics of corrugated and microgrooves surfaces, respectively. In these studies, they reported a strong dependence of the contact angle on the geometry of the grooves.…”
mentioning
confidence: 99%
“…This case was classified as ''Mixed Pinning". On the surfaces of plenty of natural and industrial products (e.g., micro channels [51], leaves of plants [52][53][54] and feather of birds [55]), the second and third states are most common. In these cases, the contact line is difficult to cross the defects, leading to the directional spreading of the droplet along the grooves on channeled surfaces [5], or the immersion of liquids on super-hydrophobic surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…为了探究非极 性C−C键与极性B−N键对水和衬底的相互作用的影 响, Li和Zeng [2] 采用第一性原理分子动力学模拟观察 了包含125个水分子的水滴分别悬浮在被固定住的石 墨烯和h-BN表面, 并测量其浸润角. 关于第一性原 理的精确度, 文献 [38]通过调节碳原子与SPCE模型 水的相互作用, 获得了与实验值接近的接触角; 而Li 和Zeng [2] [40] 和电 润湿的内容 [41] [2] Figure 1 (Color online) Snapshots of a water nanodroplet (125 water molecules) during the time evolution (in unit of ps) of the wetting process on a graphene sheet at 298 K (a), 385 K (b), and on the BN sheet at 385 K (c) [2] 时间较长, 是润湿溶解的主要成分. 而对于电溶解, 顾名思义即通过调节电压来控制界面液滴的状态.…”
Section: 纳米尺度下的润湿unclassified